Persepsi Siswa Laki-Laki Terhadap Seni Tari Kelas VIII Di SMP Negeri 1 Payakumbuh - Gustin Eliza; Susmiarti Susmiarti (SENDRATASIK UNP, 2020)
This study aimed to identify, reveal, and describe the perceptions of male students towards the learning of dance arts at the 8th grade level of SMP Negeri 1 Payakumbuh. The type of research used was qualitative research with a descriptive approach. For obtaining the data, the research used primary data and secondary data. The instruments in this study were the researchers themselves and were assisted with supporting instruments such as stationery and cameras. Techniques of data collection were completed by observation, interviews, literature study and documentation. The results of interviews indicate that many things that must be addressed by the school in order to improve the learning outcomes of male students. All the filled questions, male students tend to lead to intrinsically negative rather than positive. It can be seen by the lack of attention, interests and desires from within themselves to be interested in learning dance. Extrinsically, the more negatively leads because male students tend to lack confidence due to ridicule and others laughing at them. Thus, increasing the perceptions and motivations of male students in participating in dance art learning is essential, which can be supported by giving understanding to male students, to better understand dance learning delivered by their art and culture teachers. The results showed that male students' perceptions of dance learning at the 8th grade level of SMP Negeri 1 Payakumbuh were not pleasant, it can be seen in the evaluation statements that tend to be less competent and the results of interviews mostly had negative perceptions in dance art learning.